Pengaruh Lama Waktu Biofermentasi Chromolaena Odorata dengan Sumber Karbon Gula Lontar Cair terhadap Kandungan serta Kecernaan In Vitro Bahan Kering dan Bahan Organik - Kurnia; Dami Dato, Twenfosel O.; Benu, Imanuel (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aimed to analyze the effect of biofermentation duration of Chromolaena odorata using liquid palm sugar as a carbon source on the content and in vitro digestibility of dry matter (DM) and organic matter (OM). A Completely Randomized Design (CRD) with four treatments (LB-0 = 0 days, LB-7 = 7 days, LB-14 = 14 days, LB-21 = 21 days) and four replications was applied. Each treatment included liquid palm sugar (C/N ratio of 30) and 5% rumen fluid as a starter inoculum. Observed variables included DM content, OM content, in vitro DM digestibility (IVDMD), and in vitro OM digestibility (IVOMD). Data were analyzed using ANOVA and Duncan’s test (P<0.05). Results showed the highest DM content in LB-14 (91.64%), OM content in LB-7 (90.47%), IVDMD in LB-21 (72.55%), and IVOMD in LB-21 (71.13%). Statistical analysis confirmed that biofermentation duration significantly affected all parameters (P<0.05). The study concluded that the optimal durations were 14 days for DM content, 7 days for OM content, and 21 days for in vitro DM and OM digestibility. This research recommends using fermented Chromolaena odorata as ruminant feed, with fermentation duration adjusted to specific nutritional goals.